Development of Ecologization of Tourism: Experience of Foreign Countries - Umirov Jasur Temirkulovich (Indonesian Journal of Innovation Studies, 2022)
The article considers the experience of countries that have significant natural potential and pursue an active policy for planning, regulating, supporting, promoting and monitoring ecotourism. The methods of formal-logical, comparative and institutional analysis were used during the research. It is shown that the experience accumulated by different countries in the development of ecotourism testifies both to the specifics of each of the countries and to general approaches harmonized with international recommendations and tasks to create conditions for sustainable development of tourism. Systematic approaches and innovative solutions that exist in different countries can be recommended in the “right decision” format, as they demonstrate how ecotourism can contribute to the achievement of sustainable development goals